Uncommon Legislative Attitudes: Why a Theory of Legislative Intent Needs Nontrivial Aggregation. (9th August 2021) - Tan, David
Abstract: Since the publication of Ekins's The Nature of Legislative Intent, significant attention has been paid to common attitude models of legislative intention, that is, models that require unanimity among its group members. A common interpretation of Ekins is that these common attitudes are to be preferred over aggregated attitudes. I argue that any feasible theory of legislative attitudes will require nontrivial aggregation (i.e., not based on unanimity rules alone). Two arguments are put forward in this regard: first, that nontrivial aggregation better explains uncooperative legislative behaviour and, second, that mathematical problems with aggregation apply to common attitudes as well, since they involve trivial aggregation. These arguments generalise to theories of common attitudes other than Ekins's.